Investigation of Flow and Heat Transfer Characteristics in Two-Phase Flow Through Evaporator of Diffusion Absorption Refrigerator (DAR) - Siti Masita Rakhmawati (IPTEK Journal of Proceedings Series, 2014)
The application of the cooling system becomes very important for a comfortable and almost all public buildings in Indonesia using the cooling system. The cooling system is commonly requires considerable electrical power to drive the compressor used for the vapor compression cooling system in operation. Different with the diffusion absorption refrigeration system, all cycles in the system are occurred by natural circulation where the refrigerant is pressurized (partial) lower in the evaporator is obtained with the aid of an inert gas that can be either hydrogen or helium, which is mixed with the refrigerant gas, but not also react. The study was conducted by flowing the refrigerant at the evaporator copper tube passes that are part of a diffusion absorption refrigeration machine. Long dimension of passes evaporator is 2.38875 m. The method used in this study is the experimental and numerical approach, which is using Multiphase Flow Fluent CFD 6.3. simulation to validate the experimental observations of flow.Through this study, the fenonena happened to be validated by experimental observations numerically. Also can be seen flow characteristics of refrigerant flowing along the evaporator and heat transfer phenomena that occur.